Successful ceftazidime-avibactam treatment of MDR-KPC-positive Klebsiella pneumoniae infection in a patient with traumatic brain injury: A case report - Gugliandolo, Agnese (Medicine (Baltimore), 2017)
RATIONALE: Carbapenem-resistant Enterobacteriaceae infections are a serious health care problem, because of the high mortality. Carbapenem resistance is mainly caused by carbapenemases production, including Klebsiella pneumoniae carbapenemase (KPC). Ceftazidime-avibactam is a new cephalosporin/β-lactamase inhibitor combination for the treatment of complicated urinary, intra-abdominal infections, and nosocomial pneumonia caused by gram negative, or other serious gram-negative infections. PATIENT CONCERNS: We showed the case of a 27-year-old patient, hospitalized for traumatic brain injury and chest trauma, with KPC-producing Klebsiella pneumoniae infection. DIAGNOSES: Blood and bronchial aspirate culture analysis detected an infection caused by MDR Klebsiella pneumoniae, resistant to meropenem, ertapenem, piperacillin/tazobactam, amoxicillin/clavulanic acid, aztreonam, ceftazidime, cefotaxime, cefepime, amikacin, ciprofloxacin, trimethoprim/sulfamethoxazole, colistin while it showed an intermediate sensitivity to gentamicin and was sensitive to ceftazidime-avibactam. Molecular analyses revealed that the isolate belonged to the epidemic clone sequence type 258 (ST258) carrying bla(KPC-3), bla(TEM-1), and bla(SHV-11)genes. INTERVENTIONS: After various combined antibiotic therapies without improvements, he was treated with ceftazidime-avibactam, on a compassionate-use basis. OUTCOMES: With ceftazidime-avibactam monotherapy clinical and microbiological clearance was obtained. A week after the end of the therapy microbiological analysis was repeated and a positive rectal swab for KPC-Klebsiella pneumoniae was found, becoming negative after 1 month. Moreover, the patient did not show any relapses for up to 18 weeks. LESSONS: This case indicates that ceftazidime-avibactam monotherapy could be efficacious against KPC positive Klebsiella pneumoniae infections.